Use of Shelter Variations for Growing Giant Prawns (Macrobrachium Rosenbergii De Man) in Swamp Ponds - Pahmi Ansyari; Slamat (Formosa Journal of Sustainable Research, 2023)
One of the leading commodities in the fishery sector which is prospective is giant prawns, so its development is needed. This study aims to find appropriate and applicable shelters for giant prawn cultivation in swamp ponds. The study was conducted in Anjir Muara Village, South Kalimantan with a design to test three swamp models: Pond A: bamboo strip shelter; Pond B: shading area + staking shelter and Pond C: living plant shelter (water hyacinth). The results showed that the lowest relative growth was in treatment A which was 214.4% and feed conversion was 2.78; followed by treatment B 275.9% and 2.66 and the highest growth and feed efficiency was treatment C, namely 274.9% and 2.51. The ANOVA results also showed that there were differences between treatments, where treatment C was very significantly different compared to other treatments. Thus treatment C, namely water plant shelter in the form of water hyacinth, is best applied in giant prawn ponds